The Effectiveness of the 3W2H Strategy in Writing Explanatory Texts: Experiences Learned from Indonesian Learners - Alfi, Kunti Zahrotun; Syamsi, Kastam (JOLLT Journal of Languages and Language Teaching, 2024)
Writing explanatory text is a complex skill and requires a deep understanding of the topic, so strategies are needed that can help. This research aims to test the effectiveness of the 3W2H strategy in learning to write explanatory texts in high school. The research design uses quantitative with a quasi-experimental design. The research population was all class XI students at SMAN 1 Mojolaban, totaling 354 students. Samples were taken using cluster random sampling techniques so that 42 students were obtained as the experimental class and 48 students as the control class. Data is collected through performance tests. Research validity uses content validity, namely consulting experts. The collected data was then analyzed using ANOVA and Scheffe’s test. The research results showed that the average pre-test and post-test results for writing explanatory text for the experimental group using the 3W2H strategy were 58.48 and 83.14, while for the control group it was 61.92 and 70.3. These results show that the experimental group increased by 42.21%, while the control group increased by 13.53%. Apart from that, the p value is <0.001 or smaller, so it can be concluded that there is a significant difference in the posttest results of the experimental and control groups. Furthermore, the Scheffe test results show a p value <0.01 or smaller than 0.05, so the research shows that the 3W2H strategy is more effective than conventional strategies. These results indicate that the 3W2H strategy can be an alternative in writing explanatory text.